Implementasi Falsafah Tut Wuri Handayani pada Kurikulum Sekolah: Implementation of Tut Wuri Handayani Philosophy in the School Curriculum - Zainullah, Zainullah; Simanjuntak, Nensy Megawati; Huda, Nuril; Said, Abdurrahman (Thawalib: Jurnal Kependidikan Islam, 2024)
Philosophy plays an important role in shaping meaningful educational systems. Many schools develop curricula without considering philosophy, resulting in meaningless learning for students. This research aims to explain the application of the philosophy of Tut Wuri Handayani in the curriculum of MTs Al-Mardliyyah Pamekasan using a qualitative case study approach. Data were collected through interviews, observations, and documentation, then processed through reduction, presentation, and drawing conclusions. The implementation of the Tut Wuri Handayani philosophy includes honesty, fairness, good moral character, and motivation for students to learn well. Challenges such as laziness, shyness, and pessimism are addressed with strategies of awareness, understanding, and changing students' mindset. The impact is that students develop into better individuals morally, caring for their peers and the environment, and forming productive and adaptive learning processes. In conclusion, the implementation of the philosophy has been successful with positive effects on schools, teachers, and students. This research contributes as a reference for schools to apply philosophical aspects in education and learning.